La araldica nell'iconografia dei santi - Camelliti, Vittoria (Eikón / Imago, 2025)
The iconographic attributes of saints are not always classifiable as heraldic signs: in most cases they are generic emblems, functional to the recognition of the various characters. The saint (whose image is often assumed to be a heraldic sign), can be qualified heraldically by attributes that are proper to him and that identify him as such (as in the case of the crusader ensign of St. George or the lily cope of the Angevin saint Ludwig of Toulouse); or by 'external' attributes that requalify him in an identity sense, as is the case with the patron saints represented as standard-bearer. In the absence of specific attributes, the heraldic qualification of the saints is possible thanks to the inclusion of the elements of a coat of arms (figures and colours) on their robes, within the backgrounds and in other details of the composition. Figurative strategies are varied and employed in similar ways with reference to both civic heraldry and family heraldry in private devotional contexts.